Social determinants of employee selection and interviewing - Lisowski, Olaf; Grajek, Mateusz (Journal of Education, Health and Sport, 2023)
The problem of effective personnel planning was and is an indispensable part of the management of any enterprise. Every owner makes every effort to ensure that the people employed achieve the established goals and strategies of the organization, thereby contributing to the growth of prestige and expansion of capital. A significant capital of any organization is personnel, or human capital, which is why the proper selection of employees is such an important element. For some time now, organizations have been making every effort to ensure that employees are not only properly educated and trained, but are well aligned with the company’s mission. Large corporations, want to have an employee as if "on their own," so the goals of both the employer and the employee are important. People for whom professional success is not the most important thing would not be able to find their way in a large international organization. The recruitment and selection process is therefore a key element to check whether a candidate is the right person and in the right place.